3D printing throws a wrench in the works for the Craftsman brand - Allen, Charlotte, active 2019, (SAGE Knowledge. Cases., 2019)
Frances, a marketing consultant, was contacted by a former colleague, Rupert, who is now the brand manager for Craftsman tools. Rupert is concerned about a video depicting the apparent 3D printing of a Craftsman wrench. The case deals with the current and future impact of 3D printing and social media on branding, business strategy, and distribution. Students are put in the situation of a marketing consultant who must determine what advice to impart to the Craftsman brand manager as he navigates the impacts of emerging technologies.